Emergency medical service utilization among acute ischemic stroke patients in Beijing: An observational study - Ding, Kexin; Chen, Hui; Wang, Yong; Liu, Hongmei; Ceceke, Bayier; Zhang, Wei; Geng, Ling; Deng, Guifang; Sun, Tao; Zhang, Wenzhong; Wu, Yiqun (Frontiers in Neurology, 2022)
Objective To investigate emergency medical service (EMS) utilization and its associated factors in patients with acute ischemic stroke (AIS), and further explore the urban-rural differences. Methods Medical records for AIS in all emergency departments in Beijing were obtained from the Beijing Emergency Care Database from Jan. 2018 to Dec. 2021. EMS utilization was described and factors associated with EMS use were examined by multivariable logistic regression models with the generalized estimating equations. Results were compared between urban and rural districts. Results A total of 24,296 AIS patients were included in the analysis, and 11,190 (46.1%) were transported to hospitals by EMS. The percentage of EMS usage in urban areas was significantly higher than that in rural areas (53.6% vs 34.4%, P<0.001). From 2018 to 2021, EMS utilization was on the increase (P-value for trend <0.001) with a higher average annual growth rate in rural areas (12.6%) than in urban (6.4%). Factors associated with EMS utilization were age (OR: 1.20 per 10-year increase, 95% CI: 1.17-1.23), NIHSS scores, off-hour arrival (OR: 1.32, 95% CI: 1.23-1.37), treatment in tertiary hospitals (OR: 1.75, 95% CI: 1.60-1.92), and possessing comorbidities such as coronary artery disease (OR: 1.15, 95% CI: 1.17-1.24), atrial fibrillation (OR: 1.56, 95% CI: 1.41-1.73), prior stroke (OR: 0.84, 95% CI: 0.78-0.90) or dyslipidemia (OR: 0.78, 95% CI: 0.71-0.85). Conclusion This study demonstrated an inadequate use of EMS among AIS patients in Beijing, especially in rural areas, and revealed several associated factors. Enhanced education programs and EMS accessibility are necessary particularly for high-risk individuals and regions.